Contrastive Analysis Of Idiom Translation: Literal vs. DeepL in Adele’s Song “Someone Like You” Into Indonesian - Yuni Maria Manullang; Masta Artani Damanik; Diane Sarima Lestari Simbolon; Sarah Nasrani Gea; Poster Sagala (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2025)
This study investigates the challenges and strategies involved in translating English idioms into Indonesian, with a particular focus on Adele's song "Someone Like You." The research employs a qualitative descriptive approach and utilizes contrastive analysis, with a focus on three quality indicators: accuracy, naturalness, and acceptability. The findings indicate that literal translation can result in statements that are either uncomfortable or incomprehensible in the target language, thereby leading to a loss of the intended meaning of the idiom. In contrast, the neural machine translation of DeepL demonstrated a significantly higher success rate, achieving an accuracy of 93.33% across the analyzed idioms. In comparison, the literal translation exhibited a substantially lower accuracy of 42.22%. This exemplifies the idiomatic fluency and contextual awareness of DeepL; nevertheless, human interaction remains imperative to preserve the emotional depth and cultural subtlety of literary texts. This research underscores the potential for a symbiotic relationship between technology and human aptitude, particularly in artistic domains such as music, where the translation of idioms can be particularly salient. Subsequent research endeavors may involve a more extensive investigation of idiom translation across genres and languages, with the objective of promoting the development of emotionally intelligent machine translation tools.